Effect of Dipeptidyl Peptidase-4 Inhibitors on Renal Outcome in Diabetes Mellitus: A Systematic Review and Meta-analysis (Asian Journal of Pharmaceutics (AJP), 2024)
Diabetic nephropathy is a common microvascular consequence, described by a persistent rise in albuminuria ora considerable fall in the predictable estimated glomerular filtration rate (eGFR). Dipeptidyl peptidase-4 (DPP-4) inhibitors are frequently utilized to treat diabetes mellitus (DM), although it’s unclear how significant thesedrugs are in terms of specific renal outcomes (RO). This study aims to determine the impact of DPP-4 inhibitors(DPP4-I) on renal consequences in individuals with DM. The relevant studies were searched in PubMed, GoogleScholar, and SciHub, and then filtered concurring to the exclusion and inclusion criteria. The preferred reportingitem for systematic reviews and meta-analysis criteria were adhered to, and the extracted data were evaluated usingthe RevMan software. A 95% confidence interval (CI) was calculated in addition to the overall estimate measure.I-squared (I2) statistics were used to assess the studies’ heterogeneity. The qualitative evaluations of publication biaswere done using the funnel plot. Ten randomized controlled studies with a total of 39,124 people were eligible forthe investigation. At 24 weeks, eGFR in DM patients was not substantially affected by the DPP4-I (mean differences[MD] 4.31; 95% CI −4.93, 13.54; P < 0.00001, heterogeneity I2 = 95%; P = 0.36). Further at 52 weeks also, thechanges in eGFR were found non-significant (MD 0.24 [−1.68, 2.16]) as compared to the control group (CG). Thechanges in urine albumin-creatinine ratio were also found non-significant as compared to the CG. The adverse eventsin the DPP4-I groups were also found non-significant as compared to the CG which indicates the safety of DPP4-I.Overall, more randomized clinical trials are required to confirm the exact role of DPP4-I on RO in DM.